The process of purification of the student structure of the higher school of the South of Russia in 1924: priorities and results - I. V. Lyubeznyi; S. M. Smagina (Гуманитарные и юридические исследования)
The article studies the process of extensive academic and qualitative inspection of the student body of the higher school of Southern Russia (South-Eastern Russia at that time) made in 1924. The study is based on archival documents of territorial and local inspection commissions, as well as students’ appeals deposited in the funds of the State Archive of the Rostov Region. The official goal of the inspection was to ease the overcrowding of universities and to get rid of the «dead weight» meaning students who did not fit the criteria of a «red» specialist capable of benefiting the state. The authors attempted to determine whether the local commissions properly understood their tasks and the conditional boundary between academic and qualitative approaches, which led to the conclusion of a significant dependence of the inspection process on the mood of the local inspection commissions, often too keen on the class- based approach in their work. Another conclusion is the poor effectiveness of the inspection process itself, which did not lead to solving the overcrowding of the higher school problem, but once again alarmed the students. An analysis of the appeals of expelled students led to the conclusion of a high level of antagonism not only among the student body, but also in Soviet society in general, which was expressed, first of all, in searching for internal enemies. A student who had joined the White Army during the Civil War and failed to conceal it was often condemned to be expelled or to be denounced. Moreover, as an analysis of the reactions of the students has revealed, the purge also negatively affected the proletarian student body, which was forced to work every day and actually struggle for its survival under conditions of extreme material insecurity, leading to poor academic performance.